ANALYSIS OF PANCASILA STUDENT PROFILES REPRESENTED IN ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOLS - Anisa, Ike; Onggo, Margaret; Indrayanto, Bayu (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2024)
Education is an effort to equip individuals with knowledge and instill character values to enhance students' future self-quality. This study analyzes the implementation of the Pancasila Student Profile (P3) in English textbooks for class X SMA/MA. The six elements of P3 include: 1) Faith, piety to God Almighty, and noble character; 2) Global diversity; 3) Collaboration; 4) Independence; 5) Critical reasoning; and 6) Creativity, serving as a framework to understand student characteristics. Using a qualitative approach and content analysis, this research involved identifying and categorizing text samples (e.g., words and sentences) to evaluate the representation of P3 dimensions. Findings reveal that the textbooks reflect behaviors and values aligned with the P3 dimensions. These include habitual worship and prayer, acceptance of differing perspectives, effective group discussions, critical problem-solving, and independent, wise behavior reflecting responsibility as Pancasila students. Results are presented in a checklist table, highlighting the integration of P3 values within the textbooks.